Water washing liquid, positive pole piece, preparation method of positive pole piece, pole piece and battery

By adding lithium-containing additives to the water washing solution, the lithium nickel cobalt manganese oxide positive electrode material is washed, which solves the problem of residual alkali and excessive dissolution of lithium on the surface of high-nickel materials, and improves the stability and electrochemical performance of the material.

CN119614307APending Publication Date: 2025-03-14ENVISION DYNAMICS TECH (JIANGSU) CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411720135.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

在使用锂镍钴锰氧化物正极材料时,高镍材料表面残留较多残碱,导致凝胶化现象,且水洗过度会导致锂过度溶出,降低材料的结构稳定性和电化学性能。

Method used

The positive electrode material is washed with a water wash solution containing lithium additives. By controlling the concentration of lithium ions and the type of additives, the water wash effectively removes residual alkali, while avoiding excessive dissolution of lithium, forming a uniform cladding layer to improve the stability of the material.

Benefits of technology

The residual alkali on the surface of the positive electrode material is effectively removed, which avoids excessive lithium dissolution, reduces the deviation between the internal lithium content of the material and the external surface of the material, and improves the structural stability and electrochemical properties of the positive electrode material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119614307A_ABST
    Figure CN119614307A_ABST
Patent Text Reader

Abstract

According to the water washing liquid, the positive pole piece, the preparation method of the positive pole piece, the pole piece and the battery, on the premise that the temperature of the water washing liquid and the solubility of lithium at the temperature are certain, due to the fact that the water washing liquid comprises the lithium-containing additive, part of lithium is dissolved in the water washing liquid, and the dissolving amount of lithium which can be continuously dissolved in the water washing liquid is reduced. Therefore, when the water washing liquid is used for washing the positive electrode material, the dissolving amount of residual alkali capable of being dissolved in the water washing liquid is reduced, so that the water washing liquid is used for excessively washing the surface of the positive electrode material to ensure that part of lithium is reserved on the surface of the positive electrode material, so that lithium in the positive electrode material is prevented from being dissolved out, sufficient lithium is ensured to be contained in the positive electrode material, and meanwhile, the service life of the positive electrode material is prolonged. As internal lithium cannot be dissolved out, the deviation between the lithium content in the positive electrode material and the lithium content on the outer surface can be reduced, and the structural stability of the positive electrode material is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of energy storage technology, and in particular to a water washing liquid, a positive electrode plate and a preparation method thereof, a plate and a battery. Background Art

[0002] Lithium nickel cobalt manganese oxide (LiNi x Co y Mn z O2, x+y+z=1, z>0, y>0, z>0, referred to as NCM) positive electrode material is widely used in high energy density power battery system because of its high theoretical specific capacity (270+mAh / g). After sintering NCM using nickel cobalt manganese hydroxide precursor and lithium source, a lot of residual alkali remains on the surface of NCM, especially high nickel NCM (Ni content greater than 80%). In the existing production process, the residual alkali on the surface of NCM is cleaned by a water washing process. Summary of the invention

[0003] In view of this, the purpose of the present application is to provide a water washing solution, a positive electrode plate and a preparation method thereof, a plate and a battery.

[0004] Based on the above objectives, the first aspect of the present application provides a water washing solution, which includes water and a lithium-containing additive.

[0005] Optionally, the concentration of lithium ions in the water washing liquid is 0.8 to 1.2 mol / L.

[0006] Optionally, the lithium-containing additive is at least one of LiOH, Li2O2, Li2CO3, Li2C2O4, LiF, Li2BO3, LiCl, LiAlO2 and Li4Ti5O.

[0007] The second aspect of the present application provides a method for preparing a positive electrode material, comprising:

[0008] The water washing solution described in any one of the first aspects above is used as a cleaning agent to wash the pre-product obtained by sintering the positive electrode material precursor and the lithium source to obtain the positive electrode material.

[0009] Optionally, the mass ratio of the pre-product to the water washing liquid is 6:(2-6).

[0010] The third aspect of the present application provides a positive electrode material, wherein the lithium content on the outer surface of the positive electrode material particles and the lithium content inside the positive electrode material particles meet the condition: |m1-m2| / m1*100%<5%, wherein m1 is the lithium content on the outer surface of the positive electrode material particles, and m2 is the lithium content inside the positive electrode material particles.

[0011] Optionally, the positive electrode material particles include a positive electrode material body and a coating layer coated on the outside of the positive electrode material body, the coating layer contains a coating element, and the coating element is at least one of F, B, Cl, Al and Ti.

[0012] Optionally, in the coating layer, the deviation percentage of the coating element content is less than 5%; and / or

[0013] The mass content of the coating element is 2000-50000 ppm; and / or

[0014] The molecular formula of the positive electrode material is LiNi x Co y Mn z O2, where x>0.8, x+y+z=1.

[0015] The fourth aspect of the present application provides a positive electrode plate, comprising the positive electrode material described in any one of the third aspects above.

[0016] The fifth aspect of the present application provides a battery, comprising the positive electrode plate described in the fourth aspect.

[0017] From the above, it can be seen that the water washing liquid, positive electrode plate and its preparation method, plate and battery provided by the present application, since the water washing liquid includes a lithium-containing additive, when the water washing liquid is used to wash the positive electrode material, while ensuring that the water washing effectively removes the residual alkali (such as LiOH, Li2CO3, etc.) in the positive electrode material, based on the lithium-containing additive in the water washing, lithium is dissolved, which can effectively avoid excessive dissolution of lithium in the positive electrode material, ensure that part of the lithium is retained on the surface of the positive electrode material, avoid excessive dissolution of lithium inside the positive electrode material, and ensure that the positive electrode material contains sufficient lithium; at the same time, based on ensuring the lithium content on the surface of the positive electrode material, it is possible to effectively avoid the dissolution of lithium from the positive electrode material to the surface, reduce the deviation between the lithium content inside the positive electrode material and the lithium content on the outer surface, and improve the structural stability of the positive electrode material. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] In order to more clearly illustrate the technical solutions in the present application or related technologies, the drawings required for use in the embodiments or related technical descriptions are briefly introduced below. Obviously, the drawings described below are only embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0019] Figure 1a to Figure 1e It is a schematic diagram of the EDS test results of the positive electrode material of Example 1. DETAILED DESCRIPTION

[0020] In order to make the objectives, technical solutions and advantages of the present disclosure more clearly understood, the present disclosure is further described in detail below in conjunction with specific embodiments.

[0021] It should be noted that, unless otherwise defined, the technical terms used in the following examples have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. The test reagents used in the following examples, unless otherwise specified, are all conventional biochemical reagents; the experimental methods, unless otherwise specified, are all conventional methods.

[0022] Lithium nickel cobalt manganese oxide positive electrode material (NCM) is widely used in high energy density power battery systems because of its high theoretical specific capacity (275+mAh / g).

[0023] After using nickel-cobalt-manganese hydroxide precursors and lithium sources to sinter and obtain NCM, a lot of residual alkali remains on the surface of NCM, so a water washing process needs to be added during the production process, otherwise the excessive residual alkali remaining on the surface will cause gelation during the homogenization process. For example, during the homogenization process, the residual alkali on the surface of the high-nickel ternary positive electrode material attacks the CH and CF of the binder polyvinylidene fluoride PVDF, resulting in an elimination reaction to form a C=C double bond to produce chemical crosslinking. Due to the high regularity of the PVDF chain, continuous HF removal reactions are prone to occur, which ultimately leads to the gelation of the high-nickel ternary positive electrode material.

[0024] Water washing can wash away the water-soluble residual alkali (such as LiOH, Li2CO3) on the surface of the high-nickel ternary positive electrode material. During the water washing process, the inventors found that the degree of water washing is crucial. If the degree of water washing is not enough, there will still be a lot of residual alkali on the surface of the high-nickel ternary positive electrode material, and the gelation of the high-nickel ternary positive electrode material cannot be effectively improved.

[0025] If the water washing is excessive, the Li on the surface of the material will be removed while the residual alkali is removed, resulting in a difference in the concentration of the Li element on the surface and inside the material; and when the Li on the surface of the material is removed, part of the Li in the material near the surface area moves to the surface of the material. This will cause the Li content inside the material to decrease, increase the difference between the lithium content inside the material and the lithium content on the outer surface, and reduce the structural stability of the material based on the movement of Li. In addition, the lithium content inside the material is reduced, making the material in a lithium-deficient state, and it cannot release enough Li during the charging process. + , which leads to a decrease in the capacity of the material. Especially for high nickel ternary materials (LiNi x Co y Mn z O2, x ≥ 0.8), the loss of Li+ will aggravate the Jahn-Teller effect, thus affecting the material properties.

[0026] Therefore, it is an urgent problem to improve the ternary positive electrode materials by washing them, modifying the material structure, and then improving the material performance.

[0027] Based on this, the present application provides a water washing solution for positive electrode materials, wherein the water washing solution comprises water and a lithium-containing additive.

[0028] Specifically, under the premise that the temperature of the water washing liquid and the solubility of lithium at the temperature are certain, since the water washing liquid includes a lithium-containing additive, part of the lithium has already been dissolved in the water washing liquid, resulting in a reduction in the amount of lithium that can continue to dissolve in the water washing liquid. In this way, when the positive electrode material is washed with the water washing liquid, the amount of residual alkali (such as LiOH, Li2CO3, etc.) that can be dissolved in the water washing liquid is reduced, avoiding excessive cleaning of the surface of the positive electrode material by the water washing liquid, ensuring that part of the lithium is retained on the surface of the positive electrode material, thereby avoiding the dissolution of lithium inside the positive electrode material, ensuring that the positive electrode material contains sufficient lithium, and at the same time, since the internal lithium will not dissolve, the deviation between the lithium content inside the positive electrode material and the lithium content on the outer surface can be reduced, thereby improving the structural stability of the positive electrode material.

[0029] In some embodiments, the lithium-containing additive is at least one of LiOH, Li2O2, Li2CO3, Li2C2O4, LiF, Li2BO3, LiCl, LiAlO2 and Li4Ti5O.

[0030] Specifically, when the lithium-containing additive is LiOH, Li2O2, Li2CO3, or Li2C2O4, the addition of the lithium-containing additive can reduce the amount of residual alkali that continues to dissolve in the washing liquid, thereby avoiding excessive cleaning of the surface of the positive electrode material by the washing liquid, ensuring that some lithium is retained on the surface of the positive electrode material, and thereby avoiding lithium dissolution inside the positive electrode material.

[0031] When the lithium-containing additive is an additive such as LiF, Li2BO3, LiCl, LiAlO2 and Li4Ti5O and also contains coating elements (such as F, B, Cl, Al and Ti), the lithium-containing additive can not only reduce the amount of residual alkali that continues to dissolve in the washing liquid and avoid excessive cleaning of the surface of the positive electrode material by the washing liquid, but also play a role in wet coating. In the subsequent heat treatment process, this type of lithium-containing additive can be evenly coated on the particle surface of the positive electrode material to form a coating layer, thereby reducing the side reaction between the positive electrode material and the electrolyte, thereby stabilizing the material performance.

[0032] Conventional solid-phase coating is to mix the positive electrode material with the additive in the solid phase. This method is limited by the state of the additive. If the additive is damp, the coating will be uneven, showing an island-like coating morphology. In this way, the positive electrode material that is not coated will still have a side reaction with the electrolyte, eventually causing gas production. Compared with conventional solid-phase coating, the coating layer obtained by the wet coating of the present application is more dense and uniform, and the entire area of ​​the surface of the positive electrode material particles can be evenly coated, avoiding side reactions between the positive electrode material and the electrolyte and improving the stability of the material.

[0033] In some embodiments, the concentration of lithium ions in the water washing solution is 0.8-1.2 mol / L.

[0034] Specifically, when the concentration of the lithium ions is 0.8-1.2 mol / L, the concentration of the lithium ions is moderate, the content of the lithium-containing additive in the water washing liquid is moderate, and the amount of lithium dissolved in the water washing liquid is moderate, so that the amount of lithium that can continue to dissolve in the water washing liquid is moderate. When the water washing liquid is used to wash the positive electrode material, since the amount of lithium that can continue to dissolve in the water washing liquid is moderate, the amount of residual alkali on the surface of the positive electrode material that can be washed away by the water washing liquid is moderate, and then the amount of lithium that finally remains on the surface of the positive electrode material is moderate, which can avoid the gelation of the positive electrode material and the dissolution of lithium inside the positive electrode material to reduce the capacity. In addition, for some lithium-containing additives that also have coating elements (such as F, B, Cl, Al and Ti), adding an appropriate amount of lithium-containing additives can form a layer of lithium-containing additive coating layer with a suitable thickness on the surface of the final generated positive electrode material to protect the positive electrode material, avoid side reactions between the positive electrode material and the electrolyte, and improve the stability of the material.

[0035] When the concentration of lithium ions is less than 0.8 mol / L, the concentration of lithium ions is low, and the content of lithium additives in the water washing solution is low, which will cause excessive cleaning of the material surface, resulting in less residual lithium on the material surface, causing the amount of lithium to fail to meet the material's own demand for surface lithium. Therefore, some lithium inside the material will precipitate, resulting in internal lithium deficiency, and the internal lithium deficiency will cause the material to be in a lithium-deficient state, and a sufficient amount of Li cannot be removed during the charging process. + , which results in a decrease in the capacity of the material.

[0036] When the concentration of lithium ions is greater than 1.2 mol / L, the concentration of lithium ions is high, and the content of lithium-containing additives in the water washing solution is high, which can only wash away a small amount of residual alkali on the surface of the material, so that the amount of residual alkali left on the surface of the positive electrode material is relatively large. More residual alkali causes the positive electrode material to gel during the homogenization process. In addition, too much content of lithium-containing additives will eventually result in too much lithium-containing additives being coated on the outer surface of the positive electrode material, thereby increasing the resistance and ion transmission resistance of the positive electrode material, reducing the ion transmission performance of the material, and further reducing the electrochemical performance of the material.

[0037] Exemplarily, the concentration of the lithium ions can be 0.8mol / L, 0.81mol / L, 0.82mol / L, 0.83mol / L, 0.84mol / L, 0.85mol / L, 0.86mol / L, 0.87mol / L, 0.88mol / L, 0.89mol / L, 0.90mol / L, 0.91mol / L, 0.92mol / L, 0.93mol / L, 0.94mol / L, 0.95mol / L, 0.96mol / L, 0.97mol / L, 0.98mol / L, 0.99mol / L, 1mol / L, 1.1mol / L, 1.2mol / L.

[0038] Further, the concentration of the lithium ion is preferably 0.85-0.95 mol / L. When the concentration of the lithium ion is 0.85-0.95 mol / L, the concentration of the lithium ion is more suitable, the content of the lithium additive in the water washing liquid is more suitable, the amount of lithium dissolved in the water washing liquid is more suitable, and the amount of lithium that can continue to dissolve in the water washing liquid is more suitable. When the water washing liquid is used to wash the positive electrode material, the amount of alkali that finally remains on the surface of the positive electrode material is more suitable.

[0039] The present application also provides a method for preparing a positive electrode material, comprising:

[0040] The water washing solution described in any of the above embodiments is used as a cleaning agent to wash the pre-product obtained by sintering the positive electrode material precursor and the lithium source to obtain the positive electrode material.

[0041] Specifically, the pre-product after sintering the positive electrode material precursor (such as nickel cobalt manganese hydroxide) and the lithium source is the first sintering product in the NCM preparation process.

[0042] When the pre-product is washed with water using a washing liquid as a cleaning agent, the washing liquid can be cooled in advance and the washing temperature can be controlled at 8-10°C. This is because the solubility of residual alkalis such as LiOH and Li2CO3 in water gradually increases with the increase in temperature. Controlling the temperature of the washing liquid at 8-10°C can reduce the excessive dissolution of LiOH and Li2CO3, and less Li is dissolved (at 10°C, the solubility of Li2CO3 is 1.43g / 100gH2O, and the solubility of LiOH is 12.7g / 100g H2O).

[0043] Furthermore, the time for adding the pre-product to the washing liquid is controlled within 5 to 15 seconds. After the feeding is completed, the inner wall of the container is rinsed to prevent insufficient washing due to the material sticking to the wall. Stir for 1 to 3 minutes to dissolve the residual alkali in the material in the washing liquid. Among them, the feeding time and stirring time need to be strictly controlled to avoid excessive washing due to too long time, which eventually leads to internal lithium precipitation, and to avoid insufficient cleaning due to too short time, so that too much residual alkali remains on the surface of the positive electrode material.

[0044] After washing, the material is filtered to separate water and material. The filter cloth with appropriate pore size should be selected according to the particle size of the material to ensure that the material remains on the filter cloth and the liquid can pass through the filter holes. In particular, it is necessary to avoid excessive material loss due to too large pore size, resulting in waste, or prolonged filtration time due to small pore size.

[0045] For example, when the diameter of the positive electrode material is 12 μm, the filter cloth that can be used is 2000 mesh. Depending on the particle size, the mesh number of the filter cloth can be adjusted appropriately, as long as it is ensured that the filter holes only pass water during filtration and leave the material on the filter cloth.

[0046] The filtered dry material is dried. Exemplarily, the drying temperature is 70-80°C, and the drying time is adjusted according to the material properties and the moisture content of the filter cake, generally 5-8 hours, and the moisture content of the dried sample is <800ppm.

[0047] In some embodiments, the preparation method further includes: mixing a lithium source, a nickel source, a cobalt source and a manganese source, calcining for the first time, and crushing to obtain a pre-product; and / or calcining the positive electrode material for a second time to obtain a repaired positive electrode material.

[0048] Specifically, the ratio of the amount of lithium in the lithium source to the total amount of transition metal nickel, cobalt and manganese in the nickel source, cobalt source and manganese source can be 1.01 to 1.05, preferably 1.03. In this way, the contents of lithium, nickel, cobalt and manganese in the finally prepared positive electrode material can be ensured to meet the requirements.

[0049] The temperature of the first calcination may be between 720 and 750° C., and the time of the first calcination may be between 9 and 11 hours.

[0050] After the first calcination, the material needs to be crushed to obtain a pre-product. The crushing parameters are adjusted according to the specific conditions of the mechanical mill to disperse the particles without damaging their surface.

[0051] Then, the pre-product is added into a water washing solution, stirred, filtered and dried to wash away the residual alkali on the surface of the pre-product, and finally the positive electrode material is obtained.

[0052] Finally, the positive electrode material is calcined for a second time to obtain a repaired positive electrode material. The second calcination temperature can be 300-400° C. for 6 hours to repair the grain boundaries and improve the long-term performance of the material.

[0053] In some embodiments, the mass ratio of the pre-product to the water wash liquid is 6:(2-6).

[0054] Specifically, when the mass ratio of the pre-product to the water washing liquid is 6:(2-6), the amount of the water washing liquid is moderate, ensuring that the water washing can be carried out normally and the water washing effect is good.

[0055] When the mass ratio of the pre-product to the water washing liquid is greater than 6:2, the amount of the water washing liquid is too small to meet the water washing demand, which may result in unclean water washing and may also cause the water washing equipment to fail to operate normally.

[0056] When the mass ratio of the pre-product to the washing liquid is less than 6:6, the amount of washing liquid is too much. Adding too much washing liquid on the basis of the washing effect that can already be achieved will cause a waste of the washing liquid, and too much waste liquid will be generated after washing, greatly increasing the processing cost.

[0057] The present application also provides a positive electrode material, which is prepared by any of the preparation methods described above.

[0058] The lithium content on the outer surface of the positive electrode material particles and the lithium content inside the positive electrode material particles meet the condition: |m1-m2| / m1*100%<5%, wherein m1 is the lithium content on the outer surface of the positive electrode material particles, m2 is the lithium content inside the positive electrode material particles, and the units of m1 and m2 can be ppm.

[0059] Among them, in the radial direction of the maximum inscribed circle of the positive electrode material particle, the direction from the center of the maximum inscribed circle toward the outer surface of the positive electrode material particle is the direction from inside to outside, that is, the position close to the center of the maximum inscribed circle is the inside, and the position far from the center of the maximum inscribed circle is the outside.

[0060] Specifically, when the lithium content on the outer surface of the positive electrode material particles and the lithium content inside the positive electrode material particles meet the condition: |m1-m2| / m1*100%<5%, it means that the difference between the lithium content on the outer surface of the positive electrode material particles and the lithium content inside the positive electrode material particles is very small, further indicating that the internal lithium has not dissolved to the outside and there is no lithium-deficient state inside.

[0061] In some embodiments, the positive electrode material particles include a positive electrode material body and a coating layer coated on the outside of the positive electrode material body, the coating layer contains a coating element, and the coating element is at least one of F, B, Cl, Al and Ti.

[0062] Specifically, the coating elements F, B, Cl, Al and Ti may exist in the form of ions or in the form of compounds. Exemplarily, the coating elements may exist directly in the form of LiF, Li2BO3, LiCl, LiAlO2 and Li4Ti5O.

[0063] That is to say, when the lithium-containing additive is a lithium-containing additive containing a coating element, such as LiF, Li2BO3, LiCl, LiAlO2 and Li4Ti5O, the finally formed coating layer can exist directly in the form of LiF, Li2BO3, LiCl, LiAlO2 and Li4Ti5O, or in the form of fluoride ions, boron ions, chloride ions, aluminum ions and titanium ions.

[0064] The presence of the coating layer can protect the main body of the positive electrode material, avoid side reactions between the main body of the positive electrode material and the electrolyte in the battery, and improve the stability of the positive electrode material.

[0065] In some embodiments, in the positive electrode material, the mass content of the coating element is 2000 to 50000 ppm.

[0066] Specifically, when the mass content of the coating element is 2000-50000 ppm, the content of the coating element is moderate. When the coating element is evenly distributed on the outer surface of the main particles of the positive electrode material, the thickness of the coating layer is moderate. This can ensure that the coating layer plays a role in coating the main body of the positive electrode material and improving stability, and can also avoid the existence of the coating layer affecting the electrical properties of the positive electrode material.

[0067] When the mass content of the coating element is less than 2000ppm, the content of the coating element is too small to form a uniform coating layer on the outer surface of the main particle of the positive electrode material. For example, only point coating can be performed. The point coating causes the coating layer to be unable to completely cover the entire outer surface of the main particle of the positive electrode material. There will still be part of the outer surface that is not coated. The uncoated outer surface will still undergo side reactions with the electrolyte, thereby affecting the stability of the positive electrode material.

[0068] When the mass content of the coating element is greater than 50,000 ppm, the content of the coating element is too much, so that the thickness of the coating layer formed on the outer surface of the positive electrode material main particle is too thick. Although it can effectively protect the positive electrode material main body, it will increase the resistance and ion transfer resistance of the positive electrode material, reduce the material's ion and electron transfer performance, and thus reduce the material's electrochemical performance.

[0069] Illustratively, in the positive electrode material, the mass content of the coating element may be 2000ppm, 5000ppm, 10000ppm, 15000ppm, 20000ppm, 25000ppm, 30000ppm, 35000ppm, 40000ppm, 45000ppm, 50000ppm, etc.

[0070] Furthermore, in the positive electrode material, the mass content of the coating element is preferably 10,000 to 40,000 ppm to form a coating layer with an optimal thickness, which can significantly improve the stability of the positive electrode material without reducing the electrochemical performance of the material.

[0071] In some embodiments, in the coating layer, the deviation percentage of the coating element content is less than 5%.

[0072] In specific implementation, an energy dispersive spectrometer (EDS) is used to analyze the types and contents of the component elements in the coating layer, which can be used in conjunction with a scanning electron microscope (SEM) and a transmission electron microscope (TEM).

[0073] The energy spectrometer test results show that the deviation percentage of the coating element content in the coating layer is less than 5%, indicating that the coating element content at each position in the coating layer is not much different and the coating element content is relatively uniform, further indicating that the coating elements on the surface of the positive electrode material are coated relatively uniformly, which can effectively protect the positive electrode material body and avoid side reactions with the electrolyte.

[0074] When EDS is used for measurement, the deviation percentage = (M1+M2+…Mn) / standard value × 100%, wherein M1+M2+…Mn respectively represent the actual value of the content of the coating element at each position tested minus the absolute value of the standard value, and the standard value is the average value of each actual value.

[0075] For example, suppose that the contents of the coating elements at three locations on the outer surface of the positive electrode material particle measured by EDS are 3.4, 3.5, and 3.5, respectively.

[0076] Then, first calculate the average value of the three points μ = 1 / 3 (3.4 + 3.5 + 3.5) = 3.47, therefore, the deviation percentage = 1 / 3.47 [|3.4-3.47| + |3.5-3.47| + |3.5-3.47|] * 100% = 3.7% < 5%, which means that the content of the coating elements at each position in the coating layer is very small, and the content of the coating elements at each position is relatively uniform, which further shows that the coating elements on the surface of the positive electrode material are coated more evenly, forming a uniform coating layer.

[0077] In some embodiments, the molecular formula of the positive electrode material is LiNi x Co y Mn z O2, where x≥0.8, x+y+z=1.

[0078] NCM material preparation process. In the same synthesis route, as the Ni content increases, the sintering temperature decreases.

[0079] For example, compared with NCM materials with lower nickel content (x<0.8), the sintering temperature is higher, and a large amount of Li will volatilize during sintering, resulting in less residual alkali on the surface of the NCM material. Therefore, NCM materials with medium and low nickel content usually do not need a special water washing process to remove the residual alkali on the surface. However, when the nickel content is higher (x≥0.8), the sintering temperature is lower, and the volatilization of Li during sintering is reduced, resulting in more residual alkali on the surface of the NCM material. Especially when LiNi x Co y Mn z When x>0.8 in O2, the nickel content in the NCM positive electrode material is relatively high and its sintering temperature is relatively low, resulting in a high residual alkali content in the NCM positive electrode material. Therefore, it is very necessary to remove the residual alkali on the surface through a water washing process.

[0080] The present application also provides a positive electrode plate, comprising the positive electrode material described in any of the above embodiments.

[0081] Specifically, the positive electrode plate includes a positive electrode material, a conductive agent and a binder, and the mass ratio of the positive electrode material, the conductive agent and the binder may be 95:2.5:2.5. The conductive agent may be conductive carbon black, and the binder may be polyvinylidene fluoride.

[0082] A fifth aspect of the present application provides a battery, comprising the positive electrode plate described in any of the above embodiments.

[0083] Specifically, the battery comprises a positive electrode plate, a separator and a negative electrode plate. The negative electrode plate can be a lithium plate. The separator can be a polyethylene film.

[0084] The positive electrode plate and the battery have the technical effects of any of the above embodiments, which will not be elaborated here.

[0085] The present invention is further described below through specific embodiments.

[0086] Example 1

[0087] A water washing liquid comprises water and a lithium-containing additive, wherein the concentration of the lithium ions is 0.85 mol / L and the lithium-containing additive is LiF.

[0088] A method for preparing a positive electrode material, comprising:

[0089] The pre-crushed pre-product is added to the water washing solution described in any one of the first aspects above, stirred, filtered and dried to obtain the positive electrode material.

[0090] Among them, the pre-product is a high nickel ternary cathode material (LiNi 0.92 Co 0.05 Mn 0.03 O2 is a secondary spherical particle composed of primary particles of 400-600nm, and the secondary sphere diameter is 10.5μm).

[0091] The feeding time is 15 seconds, the stirring time is 1 to 3 minutes, and the mass ratio of the pre-product to the water washing liquid is 6:4.

[0092] A positive electrode material is prepared by the above preparation method, wherein the lithium content on the outer surface of the positive electrode material particles and the lithium content inside the positive electrode material particles meet the condition: |m1-m2| / m1*100%<5%, wherein m1 is the lithium content on the outer surface of the positive electrode material particles, and m2 is the lithium content inside the positive electrode material particles.

[0093] The positive electrode material particles include a positive electrode material body and a coating layer coated on the outside of the positive electrode material body, wherein the coating layer contains coating element fluorine. In the coating layer, the deviation percentage of the coating element content is less than 5%. In the positive electrode material, the mass content of the coating element fluorine is 2000ppm.

[0094] A positive electrode sheet includes a positive electrode material, conductive carbon black and polyvinylidene fluoride in a mass ratio of 95:2.5:2.5. The preparation method of the positive electrode sheet includes the following steps: first dissolving polyvinylidene fluoride in a solvent N-methyl-2-pyrrolidone, then adding conductive carbon black and stirring at high speed to prepare a conductive slurry, and then adding positive electrode materials according to a proportion to prepare a positive electrode slurry with a certain viscosity. Then the prepared positive electrode slurry is evenly coated on aluminum foil, first placed in a blast drying oven at 100°C for 120 minutes, and finally the dried electrode sheet is rolled, cut, and made into a positive electrode sheet, and then placed in a vacuum drying oven again and dried at 105°C for 240 minutes.

[0095] A battery comprises the above-mentioned positive electrode sheet, negative electrode sheet and separator. The negative electrode is a lithium sheet, the separator is a polyethylene film, and the positive electrode sheet, negative electrode sheet and separator are assembled in a glove box to prepare a button battery (CR2032).

[0096] Example 2

[0097] The difference from Example 1 is that the lithium-containing additive is Li2BO3.

[0098] Example 3

[0099] The difference from Example 1 is that the concentration of lithium ions is 0.90 mol / L.

[0100] Example 4

[0101] The difference from Example 1 is that the concentration of lithium ions is 0.80 mol / L.

[0102] Example 5

[0103] The difference from Example 1 is that the concentration of lithium ions is 1.20 mol / L.

[0104] Example 6

[0105] The difference from Example 1 is that the concentration of lithium ions is 0.92 mol / L.

[0106] Example 7

[0107] The difference from Example 3 is that the lithium-containing additive is Li2O2.

[0108] Example 8

[0109] The difference from Example 1 is that the concentration of lithium ions is 0.98 mol / L.

[0110] Example 9

[0111] The difference from Example 1 is that the concentration of lithium ions is 0.87 mol / L.

[0112] Example 10

[0113] The difference from Example 1 is that the lithium-containing additive is LiOH.

[0114] Embodiment 11

[0115] The difference from Example 1 is that the lithium-containing additive is LiCl.

[0116] Example 12

[0117] The difference from Example 1 is that the lithium-containing additive is LiAlO2.

[0118] Embodiment 13

[0119] The difference from Example 1 is that the lithium-containing additive is Li4Ti5O 12 .

[0120] Embodiment 14

[0121] The difference from Example 1 is that the lithium-containing additive is Li2CO3.

[0122] Embodiment 15

[0123] The difference from Example 1 is that the lithium-containing additive is Li2C2O4.

[0124] Example 16

[0125] The difference from Example 1 is that the mass ratio of the pre-product to the water washing liquid is 6:2.

[0126] Embodiment 17

[0127] The difference from Example 1 is that the mass ratio of the pre-product to the water washing liquid is 6:6.

[0128] Embodiment 18

[0129] The difference from Example 1 is that the concentration of the lithium ions is 0.75 mol / L.

[0130] Embodiment 19

[0131] The difference from Example 1 is that the concentration of lithium ions is 1.4 mol / L.

[0132] Embodiment 20

[0133] The difference from Example 1 is that the mass ratio of the pre-product to the water washing liquid is 6:1.

[0134] Embodiment 21

[0135] The difference from Example 1 is that the mass ratio of the pre-product to the water washing liquid is 6:7.

[0136] Comparative Example 1

[0137] The difference from Example 1 is that the method for preparing the positive electrode material only includes step S100 to obtain a pre-product without performing a subsequent water washing process.

[0138] Comparative Example 2

[0139] The difference from Example 1 is that the water washing solution only includes water and does not include the lithium-containing additive.

[0140] The following are performance tests of the positive electrode materials obtained in each embodiment and comparative example, the pre-product obtained in comparative example 1, and the battery.

[0141] (1) Residual alkali test:

[0142] A potentiometric titrator (model 905 Ai·intelligent fully automatic potentiometric titrator) was used to titrate the residual alkali of the positive electrode materials obtained in each embodiment and comparative example and the pre-product obtained in comparative example 1 (i.e., the material before water washing) to obtain the LiOH and Li2CO3 values ​​in the material before and after water washing.

[0143] (2) Electrochemical performance test

[0144] First, the prepared button battery was activated by charging and discharging at 0.1C at 25°C within the battery operating voltage range of 3.0V (discharge cut-off voltage) to 4.3V (charge cut-off voltage). Then the battery was tested.

[0145] At room temperature of 25°C, constant current and constant voltage charging (cut-off current of 0.05C) and constant current discharge (cut-off voltage of 3.0V) were carried out at 0.33C in the voltage range of 3.0-4.3V, and the button battery was cycled 100 times to obtain its electrochemical performance test results (the electrochemical workstation equipment model is Blue Electric M340A precision battery tester), including constant current and constant voltage charging specific capacity CCCV, constant current discharge specific capacity DC and initial coulomb efficiency ICE (ICE = first cycle discharge capacity / first cycle charging capacity), and 100-cycle capacity retention rate (100-cycle capacity retention rate = discharge specific capacity after 100 cycles / initial discharge specific capacity*100%).

[0146] (3) Energy Dispersive Spectrometer (EDS) test

[0147] EDS test was carried out on the positive electrode material to confirm the coating effect. The deviation of the coating element content measured by EDS was <5%, indicating that the elements were evenly coated on the surface of the material, and no island-shaped or block-shaped uneven coating was formed, verifying the uniformity of the surface coating layer (equipment model is NOVANanoSEM 450).

[0148] Figure 1a to Figure 1e is a schematic diagram of the EDS test results of Example 1, wherein: Figure 1a This is a schematic diagram of the EDS test results of the entire positive electrode material of Example 1. Figure 1b Schematic diagram of EDS test results of Ni content in the positive electrode material of Example 1, Figure 1c This is a schematic diagram of the EDS test results of the Co content in Example 1. Figure 1d Schematic diagram of the test results of the Mn content in the positive electrode material of Example 1, Figure 1eSchematic diagram of the EDS test results of the F content in the positive electrode material of Example 1.

[0149] Depend on Figure 1a to Figure 1e It can be seen that the Ni, Co, and Mn elements are evenly distributed on the surface of the positive electrode material after water washing, and there are obvious traces of F coating, indicating that the water-washed additive LiF is evenly coated on the surface of the positive electrode material after drying, forming an in-situ highly stable fluoride coating layer, which improves the electrochemical stability and structural stability of the material.

[0150] (4) X-ray photoelectron spectroscopy (XPS)

[0151] XPS etching is used, with each etching depth of 10nm and the deepest etching depth of 1000nm, i.e. 1μm, to detect the Li content on the surface and inside of the positive electrode material. The equipment model is ESCALAB 250Xi.

[0152] The Li content measured on the surface of the material (ie, the lithium content at a thickness of 0 nm from the outer surface along the radial direction of the material) is defined as 100%, and the Li content values ​​at various positions inside the material are converted.

[0153] Five samples were taken from each of the above embodiments and comparative examples to carry out the above test experiments. The experimental data of the parallel samples in each comparative example and embodiment were recorded, and the average value of the experimental data of the parallel samples was taken as the final experimental data. The experimental data and test results are shown in Tables 1 and 2 below.

[0154] Table 1 Experimental data list of various embodiments and comparative examples

[0155]

[0156]

[0157] Table 2 Test data list of various embodiments and comparative examples

[0158]

[0159]

[0160]

[0161] As can be seen from the above table, from the perspective of water washing effect, compared with the pre-product of Comparative Example 1 without water washing, the residual alkali content (i.e., free Li +Compared with the positive electrode material obtained by directly washing with a water washing solution without a lithium-containing additive in Comparative Example 2, the amount of residual alkali in the positive electrode materials of each embodiment increases, indicating that the water washing effect is not as thorough as that of Comparative Example 2.

[0162] Specifically, the total residual alkali of the initial material before water washing modification in Comparative Example 1 was 1329 ppm, and some LiOH and Li2CO3 were washed away after pure water washing in Comparative Example 2, and the residual alkali amount was reduced to 533 ppm, while the residual alkali of the positive electrode material after the addition of LiF additive in Example 1 increased to 928 ppm, which was higher than the residual alkali of the pure water washed material in Comparative Example 2, indicating that the washing effect was not as thorough as that in Comparative Example 2.

[0163] From the perspective of electrochemical performance, the electrochemical performance of the positive electrode material after washing with a water washing solution containing LiF additive is also greatly improved. This is because the LiF additive forms a uniform coating layer on the outer surface of the positive electrode material particles. The presence of the coating layer prevents the side reactions between the positive electrode material and the electrolyte, thereby improving the material's capacity and cycle capacity retention rate.

[0164] From the perspective of lithium content, in each embodiment of the present application, since a lithium-containing additive is added to the water washing solution, the amount of residual alkali that continues to dissolve in the water washing solution is controlled, so that the water washing is not too thorough, and the residual alkali with a suitable content on the outer surface of the material is retained, avoiding the dissolution of internal lithium. Therefore, along the radial direction, the amount of Li at a position 10nm away from the outer surface (hereinafter referred to as the "subsurface") is 97-99%. Compared with the outer surface of the particle, the internal Li amount changes less, <5%, and the Li amount from the outside to the inside changes less, so that the subsurface can be avoided. The phenomenon of lithium deficiency can be avoided, and the rate performance and capacity of the material are improved.

[0165] In Comparative Example 2, the positive electrode material was washed with pure water as the washing liquid. The XPS at a position 10nm thick from the outer surface showed that the Li amount was 6% lower than that of the outer surface. This is because the washing was too thorough when pure water was used as the washing liquid, so that the residual alkali on the surface was insufficient, causing the Li in the subsurface layer to dissolve in order to maintain the lithium amount on the surface. The Li amount at a position 20nm and 30nm thick from the outer surface recovered and was higher than the subsurface layer. The Li amount at a position 500nm and 1μm thick from the outer surface remained basically unchanged. The reduced lithium content in the subsurface layer causes the subsurface layer to be in a lithium-deficient state, and it is unable to release sufficient Li during the charging process. + , which leads to a decrease in the capacity of the material, and the lithium-poor subsurface will hinder the Li + Mutual migration reduces the ion transmission rate of the material, resulting in a decrease in rate performance.

[0166] In Example 18, the concentration of lithium ions is 0.75 mol / L. At this time, the concentration of lithium ions is low, the content of lithium additives in the washing liquid is low, and the amount of lithium dissolved in the washing liquid is small, so that the amount of residual alkali on the surface of the positive electrode material that can be washed away by the washing liquid is large, and then the amount of residual alkali remaining on the surface of the positive electrode material is small, resulting in the residual alkali amount remaining not meeting the material's own demand for the residual alkali amount, so that part of the lithium inside the material will be precipitated, resulting in internal lithium deficiency, so that the capacity of the positive electrode material is reduced, and the internal lithium deficiency will cause the subsurface of the material to be in a lithium-deficient state, and a sufficient amount of Li cannot be removed during the charging process. + , which leads to a decrease in the capacity of the material, and the lithium-poor subsurface will hinder the Li + Mutual migration reduces the ion transmission rate of the material, resulting in a decrease in rate performance.

[0167] In Example 19, the concentration of lithium ions is 1.4 mol / L, the concentration of lithium ions is relatively high, the content of lithium-containing additives in the water washing liquid is relatively high, and the amount of lithium dissolved in the water washing liquid is relatively large, so that the amount of residual alkali on the surface of the positive electrode material that can be washed away by the water washing liquid is relatively small, and thus the amount of residual alkali remaining on the surface of the positive electrode material is relatively large. The large amount of residual alkali causes the positive electrode material to gel during the homogenization process. In addition, too much content of lithium-containing additives will eventually result in too much lithium-containing additives being coated on the outer surface of the positive electrode material, thereby increasing the resistance and ion transfer resistance of the positive electrode material, reducing the ion transfer performance of the material, and thus reducing the electrochemical performance of the material.

[0168] In Example 20, the mass ratio of the pre-product to the water washing liquid is 6:1. At this time, the amount of the water washing liquid is too small, resulting in incomplete water washing.

[0169] In Example 21, the mass ratio of the pre-product to the water washing liquid is 6:7. At this time, the amount of water washing liquid is too much, and adding too much water washing liquid does not further significantly improve the water washing effect. Therefore, adding too much water washing liquid on the basis of the water washing effect that can be achieved will cause a waste of water washing liquid, and too much waste liquid will be generated after water washing, which greatly increases the processing cost.

[0170] In summary, in this application, by adding lithium-containing additives to the washing liquid, the amount of residual alkali LiOH, Li2CO3, etc. dissolved in the washing liquid during subsequent washing is reduced, thereby reducing Li dissolution, controlling the change in the amount of Li from the surface to the inside of the positive electrode material to <5%, and ensuring the stoichiometric ratio and electrochemical performance of the positive electrode material. And by reasonably selecting the washing additive, the effect of wet coating can be achieved (the deviation of the coating element content measured by EDS on the surface is <5%), and the additive can be evenly coated on the surface of the material during the subsequent heat treatment process, reducing the possibility of side reactions between the material and the electrolyte, thereby stabilizing the material performance.

[0171] Those skilled in the art should understand that the discussion of any of the above embodiments is merely illustrative and is not intended to imply that the scope of the present disclosure (including the claims) is limited to these examples. Based on the concept of the present disclosure, the technical features in the above embodiments or different embodiments may be combined, the steps may be implemented in any order, and there are many other variations of the different aspects of the embodiments of the present disclosure as described above, which are not provided in detail for the sake of simplicity.

[0172] The embodiments of the present disclosure are intended to cover all such substitutions, modifications and variations that fall within the broad scope of the appended claims. Therefore, any omissions, modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the embodiments of the present disclosure should be included in the scope of protection of the present disclosure.

Claims

1. A water washing liquid, characterized in that The water wash solution includes water and a lithium-containing additive.

2. The water washing liquid according to claim 1, characterized in that The concentration of lithium ions in the water washing liquid is 0.8 to 1.2 mol / L.

3. The water washing liquid according to claim 1, characterized in that The lithium-containing additive is at least one of LiOH, Li2O2, Li2CO3, Li2C2O4, LiF, Li2BO3, LiCl, LiAlO2 and Li4Ti5O.

4. A method for preparing a positive electrode material, characterized in that: include: The water washing liquid described in any one of claims 1 to 2 is used as a cleaning agent to wash the pre-product after sintering the positive electrode material precursor and the lithium source to obtain the positive electrode material.

5. The method according to claim 4, characterized in that The mass ratio of the pre-product to the water washing liquid is 6:(2-6).

6. A positive electrode material, characterized in that: The lithium content on the outer surface of the positive electrode material particles and the lithium content inside the positive electrode material particles meet the condition: |m1-m2| / m1*100%<5%, wherein m1 is the lithium content on the outer surface of the positive electrode material particles, and m2 is the lithium content inside the positive electrode material particles.

7. The positive electrode material according to claim 6, characterized in that The positive electrode material particles include a positive electrode material body and a coating layer coating the outside of the positive electrode material body, the coating layer contains a coating element, and the coating element is at least one of F, B, Cl, Al and Ti.

8. The positive electrode material according to claim 7, characterized in that In the coating layer, the deviation percentage of the coating element content is less than 5%; and / or The mass content of the coating element is 2000-50000 ppm; and / or The molecular formula of the positive electrode material is LiNi x Co y Mn z O2, where x>0.8, x+y+z=1.

9. A positive electrode sheet, characterized in that: The positive electrode material comprises the positive electrode material according to any one of claims 6 to 8.

10. A battery, characterized in that: Including the positive electrode sheet as described in claim 9.